Alternate-day dosing of linagliptin in type 2 diabetes patients controlled on once daily dose: A case series - Manash P Baruah; Sonali B Bhuyan; Jumi Deka; Jatin Bora; Smritisikha Bora; Murchana Barkakati (Indian Journal of Endocrinology and Metabolism, 2016)
Linagliptin, a dipeptidyl peptidase 4 (DPP 4) inhibitor with a long terminal half life, significantly inhibits the DPP 4 enzyme at a steady state up to 48 h after the last dose. The present case series examined the hypothesis that linagliptin retains its efficacy during alternate day dosing in type 2 diabetes patients when switched over from once daily (OD) dosing. Eight type 2 diabetes patients maintaining stable glycosylated hemoglobin (HbA1c) with acceptable fasting plasma glucose and postprandial glucose levels and receiving linagliptin 5 mg OD for at least 6 weeks, with a stable dose of concomitant antidiabetic medications were given linagliptin 5 mg every alternate day. The median HbA1c while on the OD regimen was 6.1% (43 mmol/mol) (range: 5.8–6.9% [40–52 mmol/mol]) and median duration of diabetes was 7 years (range: 0.75–16 years). After a median follow-up period of 21weeks,the glycemic control was maintained in all patients similar to their baseline values (median HbA1c: 6.0% [42 mmol/mol], range: 5.1–7.1% [32–54 mmol/mol]). The body weight, fasting, and random glucose levels at baseline were also well maintained at the end of treatment. Optimal glycemic status maintained in our study population favors our hypothesis that linagliptin used alternate daily after switching from initial OD dose of the drug in patients on a stable background antidiabetic medications retains its efficacy. Paradoxically, alternate day dosing may affect compliance if the patient forgets when they took the last dose. Further studies including larger cohorts are needed to validate this finding and identify patients who can benefit from the alternate day regimen.